A Novel Method for Transcranial Doppler Microembolic Signal Monitoring at the Vertebrobasilar Junction in Vertebral Artery Dissection Patients. Issue 2 (10th December 2012) - Yamaoka, Y.; Ichikawa, Y.; Kimura, T.; Sameshima, T.; Ochiai, C.; Morita, A.
ABSTRACT BACKGROUND Vertebral artery dissection (VAD) is one of the most important etiologies in young stroke patients. VAD causes ischemic stroke by embolism and transcranial Doppler (TCD) monitoring can detect microemboli originating from the dissection point as high intensity transient signals (HITS). We developed a simple but novel method of TCD monitoring at the vertebrobasilar junction in VAD patients. METHODS We placed a Welder TCD headband upside down on the patient's head and rotated it by 90°. Then we fixed a pulsed‐wave 2‐MHz TCD probe to the headband and put it on the suboccipital paramedian area of the patient. With a patient in the lateral decubitus position, the vertebrobasilar junction was identified at a depth of approximately 80 mm. RESULTS We examined 11 patients with VAD and detected HITS in 2 patients (18%). In 1 patient HITS disappeared after heparinization, and in the other patient HITS disappeared after treatment with aspirin. All of 9 HITS‐negative patients and 1 of 2 HITS‐positive patients experienced no ischemic recurrence during hospitalization. CONCLUSION We successfully detected HITS at the vertebrobasilar junction in VAD patients, which may lead not only to an appropriate choice of antithrombotic drugs but also to individual evaluation of early risk of ischemic recurrence.